2015
DOI: 10.1007/s00382-015-2919-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Gulf Stream on wintertime European blocking

Abstract: 24Wintertime blocking is responsible for extended periods of anomalously cold and dry 25 weather over Europe. In this study, the influence of the Gulf Stream sea surface temperature 26 (SST) front on wintertime European blocking is investigated using a reanalysis dataset and a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 90 publications
5
77
0
Order By: Relevance
“…In contrast, Wills et al (2016) identified the significant transient atmospheric circulation responses that lag the SST anomalies in the GS extension by several weeks, with the pattern of response characterized by the anomalous low (high) sea level pressure (SLP) over the GS region (south of Iceland). Similarly, O'Reilly et al (2017) found the northward shift of the North Atlantic eddy-driven jet and the increase in European blocking frequency in response to the GS SST front (see also O'Reilly et al 2016).…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…In contrast, Wills et al (2016) identified the significant transient atmospheric circulation responses that lag the SST anomalies in the GS extension by several weeks, with the pattern of response characterized by the anomalous low (high) sea level pressure (SLP) over the GS region (south of Iceland). Similarly, O'Reilly et al (2017) found the northward shift of the North Atlantic eddy-driven jet and the increase in European blocking frequency in response to the GS SST front (see also O'Reilly et al 2016).…”
Section: Introductionmentioning
confidence: 76%
“…The change in transient eddy activity can strengthen the formation of a blocking ridge through the anomalous convergence of the eddy vorticity flux (Hoskins and Karoly 1981;Hoskins et al 1983;Hendon and Hartmann 1982;Peng and Whitaker 1999;Seo et al 2014;O'Reilly et al 2016). To quantify the role of the barotropic transient eddy feedback, we focus on the upper-level flow and calculate the Z 250 tendency solely caused by anomalous vorticity flux convergence Z HF t from a quasigeostrophic potential vorticity equation (e.g., Lau and Nath 1990), ›Z 250 ›t…”
Section: A High-frequency Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations